Pengaruh Implementasi Kebijakan Akuntansi Aset Biologis, Praktik Good Corporate Governance Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Serta Dampaknya Terhadap Manajemen Pajak - Indah Oktanti Sembiring, Sari; Metalia, Mega (Fakultas Ekonomi Universitas Gresik, 2023)
Tax management is carried out by all companies including the agricultural sector. In practice, the impact caused by various problems related to accounting policies of biological assets, transparency, accountability, responsibility, independence, and fairness and size of the company so that the impact on financial performance. This study aims to prove empirically whether there is an influence of good corporate governance practices and company size on tax management in agricultural sector companies. Research data were collected through questionnaire instruments, face-to-face interviews and group discussion forums which were conducted in several places in Indonesia. Sampling with non probability sampling. Data were analyzed using Structural Equation Model (SEM) and Analytical Hierarchical Process (AHP) approaches. The results showed that good corporate governance practices had an effect on tax management. But company size has no effect on tax management. In addition, the findings of this study prove that alternative strategies in the form of building good and conducive communication with stakeholders and good corporate governance practices are strategic policy priorities in tax management for agricultural sector companies to improve their financial performance. The limitation of this research lies in the analysis unit of the plantation and forestry sector alone, not yet in other agricultural sectors such as livestock and fisheries that have the same characteristics as regulated in PSAK No. 69 Agriculture, namely biological transformation.